ANALISIS RISIKO KERJA PADA PROSES PEMBUBUTAN MENGGUNAKAN METODE HIRARC - Kurnia, Fikrihadi; Pradityatama, Maharsa; Gunartha, I Gusti Made Bagus Sri; Patraman, I Gusti Ngurah Agung Natria; Pramartha, I Putu Bayu (Energy, Materials and Product Design, 2023)
Poor management of occupational safety and health (OSH) has an impact on occupational accidents. This results in losses for both the individual worker and the company. Therefore, the occupational hazard accident risk analysis was carried out using the HIRARC (Hazard Identification Risk Assessment and Risk Control) method. Data collection was conducted from the business owners of SSBC (Sanggar Sarana Baja Cakra) Welding and Turning Shop, located in Cakranegara, Mataram, West Nusa Tenggara. There are 3 work activities for risk identification, namely the clamping process, the engraving process and the drilling process. The results of the analysis show that the highest level of occupational risk occurs during clamping and engraving process. For drilling, it's in low level of risk. As for risk management, it is mainly done for high-risk level. Immediate improvement is needed by providing personal protective equipment (PPE) to workers to reduce these risks. Based on these results, business owners can do evaluation on his business so occupational accidents can be in the workplace.